Impurity profiling method development and validation of metformin hydrochloride and teneligliptin hydrobromide hydrate in their combination tablet dosage form by using RP-HPLC with UV/PDA detector - B. D. Musmade; M. L. Baraskar; V. N. Ghodke; S. G. Bhope; S. Padmanabhan; K. S. Lohar (SpringerOpen, 2021)
Abstract Background An accurate, precise and robust analytical method was developed for the impurity profiling in the metformin hydrochloride and teneligliptin hydrobromide hydrate tablet. The gradient was optimized for better separation of impurities by using BDS Hypersil C18 250 × 4.6 mm, 5µ column operated at 35 °C. The octane sulfonic acid and phosphate buffer with triethylamine at pH 3.0 were used as mobile phase A, and acetonitrile was used as mobile phase B. The mobile phase was pumped at 1.0 mL/min. The gradient was optimized for better resolution, and the chromatogram was monitored at 210 nm. Results The % recovery of teneligliptin and metformin HCL observed was above 90% from LOQ level to 150%. The correlation coefficient r 2 was 0.999 for metformin HCl, teneligliptin, melamine, cyanocobalamin, teneligliptin impurity A and 0.998 for teneligliptin impurity B. The method was found unaffected by change in method variance during the robustness study. During the stress study with acid, base, peroxide and temperature, maximum degradation was observed with peroxide indicating the sensitivity of the molecule toward oxidative stress. Conclusions The developed method is precise, accurate, robust and linear and hence can be routinely used for the related substance analysis of metformin hydrochloride and teneligliptin hydrobromide hydrate tablet in the quality control laboratory at manufacturing site during the commercial manufacturing.